Previsão de guildas de dispersão e de fenologia foliar com base em atributos funcionais para espécies arbustivo-arbóreas em uma área de cerrado sensu stricto em Itirapina (SP) - Jardim, André Vitor Fleuri (2006)
There is growing recognition that classifying terrestrial plant species on the basis of their function (into functional types ) rather than their higher taxonomic identity is a promising way forward for tackling important ecological questions at the scale of communities, landscapes, and biomes. The aim of a plant ecology strategy scheme (PESS) is to express an understanding of important opportunities and selective forces that shape the ecologies of plants and to describe the general principles of plant-environment relations without taxonomic details, to provide a common language for comparing species and vegetation types worldwide. Westoby (1998) proposed a PESS for woody species consisted of three axes: 1) specific leaf area (SLA); 2) height of the canopy of the species; and 3) seed mass. These traits, leaf-height-seed (LHS), are correlated with a number of others and are fundamental trade-offs controlling plant strategies. The aim of this study was to test in a disjoint cerrado woodland site in southeastern Brazil whether traits of the LHS scheme are potential predictors of dispersal guilds. We tried to answer the following question: do the species dispersed by abiotic means present different ecological strategies to species dispersed by animals, considering the LHS scheme? Still, we tested in the same community whether specific leaf area and plant height are potential predictors of two phenological groups, that is, deciduous and evergreen species. We tried to answer the following question: are SLA and plant height related to leaf phenology? According to our results, neither dispersal guilds nor leaf phenological groups could be predicted by the functional traits studied. The similarity in SLA in both cases may be due to two factors: similar height of species (similar habitats in regard to light availability) and sclerophylly. Soil nutrient deficiency seems to lead cerrado woody species to convergent adaptative adjustments regarding both specific leaf area and height. Dispersal guilds were similar concerning seed mass, given that all zoochorous species studied were ornithochorous, whose seed mass is typically low, and abiotically dispersed species had higher than expected seed masses. In the cerrado, the latter may occur as support to the investment in high root-to-shoot ratio of biomass allocation at the seedling stage. Seeds of bird-dispersed species are limited on the size and mass because of the small size of most frugivorous birds. Additionally, in the cerrado, some plants associated with bird dispersers may have their diaspores collected by ants, which favours their seed germination.